Improving Student Pronunciation Skills Using Videos With Subtitles At SMP Al-Lathifah 2 Setu - Mishbahuddin, Ahmad (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the effectiveness of using videos with subtitles to improve the pronunciation skills of ninth-grade students at SMP Al-Lathifah 2 Setu. Mastering pronunciation is a critical aspect of learning English, especially for non-native speakers. However, many students face difficulties in accurately pronouncing words due to insufficient practice and exposure. The study employed a Classroom Action Research (CAR) methodology, implemented over two cycles, to evaluate how multimedia resources, specifically videos with subtitles, can enhance pronunciation skills. The research was grounded in social learning theory, which emphasizes the role of observation and imitation in the learning process. Students engaged with videos in English, where they could simultaneously hear the correct pronunciation and view the corresponding text. The results indicated significant improvement in students’ pronunciation, with increased engagement and confidence. In the pre-cycle assessment, only 35% of students met the minimum passing criteria, but after the intervention, the passing rate rose to 90%. This improvement suggests that videos with subtitles can provide an effective tool for enhancing pronunciation, as students were able to better imitate the pronunciation patterns observed in the videos. The study highlights the potential of multimedia tools in language education and recommends their integration into teaching practices to improve English pronunciation among students.